Study of Nitrogen-Modified Titanium Dioxide as an Adsorbent for Azo Dyes - Magdalena Janus; Julia Choina; Ewelina Kusiak; Antoni W. Morawski (Adsorption Science & Technology)
The removal of two azo dyes from aqueous solution was investigated using a highly active nitrogen-modified titanium dioxide (TiO 2 /N). This photocatalyst was prepared by pressure modification of a commercial sample of anatase, TiO 2 (supplied by Zaklady Chemiczne Police SA, Poland). The adsorption of two azo dyes (Reactive Red 198 — a monoazo dye and Direct Green 99 — a polyazo dye) onto the unmodified and nitrogen-modified TiO 2 surface was determined. Adsorption onto unmodified TiO 2 led to an isotherm which could be described by the Freundlich model, whereas that onto the nitrogen-modified TiO 2 surface was best described by the Langmuir model. The adsorption isotherms of Direct Green 99 onto TiO 2 /N from aqueous solutions at various pH values were compared with those onto unmodified TiO 2 during dye removal under UV irradiation. Such a comparison is important since it provides information as to how solutes interact with adsorbents. Zeta potential measurements of TiO 2 provided an explanation for the observed behaviour in terms of the surface charge. The IR spectrum of the photocatalyst obtained exhibited new absorption bands at 1430–1440 cm −1 which were attributed to the bending vibrations of NH + 4 and at 1535 cm −1 associated with NH 2 groups or NO 2 and NO groups.